ANALISIS PENGARUH CORPORATE GOVERNANCE TERHADAP EARNING MANAGEMENT PADA PERUSAHAAN CONSUMER GOODS YANG TERDAFTAR DI BEI 2017 - 2020 - Ayu Sheilla Rachmawati Ayu Sheilla (Management and Sustainable Development Journal, 2021)
This study investigates the effect of corporate governance on earnings management in consumer goods companies listed on the Indonesia Stock Exchange for the period 2018 – 2020. This study provides evidence that the independent variable of corporate governance consists of three variables, namely institutional ownership, size of the board of commissioners, and composition independent board of commissioners can be seen that institutional ownership and board composition variables have no significant effect on earnings management and only the size of the board of commissioners has a significant effect on earnings management. In addition, for the control variable, the results of existing research show that the influence of leverage which is not significant on earning management and firm size has a significant effect on earning management. Therefore, it can be interpreted that companies with the status of corporate governance do not significantly affect earnings management.